Statins in the chemoprevention of colorectal cancer in established animal models of sporadic and colitis-associated cancer. Issue 2 (March 2016) - Pikoulis, Emmanouil; Margonis, Georgios A.; Angelou, Anastasios; Zografos, George C.; Antoniou, Efstathios
Abstract : Despite the availability of effective surveillance for colorectal cancer with colonoscopy, chemoprevention might be an acceptable alternative. Statins are potent inhibitors of cholesterol biosynthesis. In clinical trials, statins have been found to be beneficial in the primary and secondary prevention of coronary heart disease. However, the overall benefits observed with statins appear to be greater than what might be expected from changes in lipid levels alone, suggesting effects beyond cholesterol lowering. This systematic review aimed to gather information on the possible chemopreventive role of statins in preventing carcinogenesis and tumor promotion by a diverse array of mechanisms in both sporadic and colitis-associated cancer in animal models. The MEDLINE database was thoroughly searched using the following keywords: 'statin, HMG-CoA reductase inhibitor, colon cancer, mice, rats, chemoprevention, colitis-associated cancer'. Additional articles were gathered and evaluated. There are a lot of clinical studies and meta-analyses, as well as a plethora of basic research studies implementing cancer cell lines and animal models, on the chemopreventive role of statins in colorectal cancer (CRC). However, data derived from clinical studies are inconclusive, yet they show a tendency toward a beneficial role of statins against CRC pathogenesis. Thus, more research on the molecular pathways of CRC tumorigenesis as related to statins is warranted to uncover new mechanisms and compare the effect of statins on both sporadic and colitis-associated cancer in animal models. Basic science results could fuel exclusive colitis-associated cancer clinical trials to study the chemopreventive effects of statins and to differentiate between their effects on the two types of CRCs in humans.